Future of Sustainable Management of Energy Companies in Terms of Attitudes and Preferences of the Younger Generation - Arnold Pabian; Katarzyna Bilińska-Reformat; Barbara Pabian (Energies, 2021)
The future of the energy sector depends on the younger generation. The paper presents the results of the study, the aim of which was to determine to what extent younger generation is pro-ecological and pro-social, and whether they will include pro-ecological and pro-social activities in the management of energy companies. It is especially important to implement sustainable management in the energy sector. The study found that only 33.9% of young people are highly pro-ecological and 28.6% highly pro-social. As many as 83.0% of the younger generation show low and medium interest in environmental protection. Declarations of young people concerning high degree of inclusion of pro-ecological and pro-social activities in management are at the level of 49.9% and 58.1%. However, in many cases, these intentions do not coincide with the high pro-ecological and pro-social attitude of young people. This means that their future activity for sustainable management may be low. According to the survey, the younger generation to a large extent is not prepared to continue efforts for sustainable development in the future in the energy companies.